Application of Mitra® microsampling for pharmacokinetic bioanalysis of monoclonal antibodies in rats. (20th November 2018) - Li, Hua; Bigwarfe, Tammy; Myzithras, Maria; Waltz, Erica; Ahlberg, Jennifer
Aim: Volumetric absorptive microsampling (VAM) is being increasingly applied in nonclinical pharmacokinetic studies. Although there are published results for VAM use in small molecule pharmacokinetics (PK) studies, there is limited data on the utility of VAM for protein therapeutics.Results: We describe the use of Mitra ® microsampler for blood sampling, ELISA quantitation and PK analysis of two marketed therapeutic monoclonal antibodies administered to rat. Results generated for these monoclonal antibodies using Mitra ® were compared with both serum and whole blood sampling methods in the same study.Conclusion: The low relative standard deviation among the three sets of PK data suggest that Mitra ® microsampler could be useful in early nonclinical PK studies for protein therapeutics where reduction and refinement of animal use is desirable.